Peran Kepuasan Kerja Sebagai Variabel Mediasi Pada Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada TCT Teknik - Putri, Retrin Irene; Zain, Efendy; Marhamah, Siti (Journal of Accounting, Management, and Economics Research (JAMER), 2025)
This study aims to explore the role of job satisfaction as a mediating variable in the influence of leadership style and work environment on employee performance. The main issues raised are low employee performance levels due to job dissatisfaction, suboptimal work environment, and the implementation of ineffective leadership styles. The novelty of this study lies in the comprehensive approach that integrates the three main variables in the context of an engineering company in Jakarta. The results show that leadership style and work environment significantly affect employee job satisfaction and performance, and job satisfaction mediates the relationship between leadership style and employee performance. However, job satisfaction does not mediate the relationship between work environment and employee performance. The managerial implications are that companies are advised to adopt a more inclusive leadership style, create a conducive work environment, and improve job satisfaction through training and management of employee relationships to support optimal performance.